(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Evaluation of exchange-traded financial assets fair is regarded as an essential duty in contemporary economics. Nonetheless, the significance of approaches for assessment and anticipation of potential costs is perpetually altering. This article offers a comparative examination of technical and fundamental analysis techniques, revealing their benefits and drawbacks. That features of Fundamental analysis (FA) as income, profit, profitability and the debt burden level are deemed in depth, the extent of their impact on the securities’ price is investigated. Following the study, conclusions are made regarding the progressively narrow utilization of technical examination throughout short-term and investments issue solution. An anticipation is for a more fall of FA significance as the primary technique of evaluation. To acquire those conclusions, the study utilized statistical data reveal the characteristics of exchange-traded assets while organizations got into IPOs. The information acquired demonstrate a vivid relation between the innovation element of businesses, market share and the costs. Meanwhile, the organization profit has eventually deceased to be the primary features of the business over the course of its evaluation. Plus, they investigated the relation between the fairness of exchange-traded asset assessments and quantitative easing (QE) schemes.